The Abondonment Of The Renaissance Reality In Early Mannerist Italian Painting - Uran, Pelin (Institute of Social Sciences, 2001)
As mi art movement Mannerism was bom in Florence, spread to Rome and then to other countries having an international character. The most representative pieces of the early period can be found in Tuscany region especially in Florence. A transformation period in social, religious, political and cultural fields was encountered in the beginning of the sixteenth century primarily in Italy then in the other countries in Europe. It was lived right after the dominance of rationality, objectivity and mathematical truth of the Renaissance and with the help of the historical events, geographical improvement, technological and scientific innovations, the values of the former century changed for good and were replaced with new ones. The transformation period can clearly be observed in arts due to the effect of subsidiary events. As the representatives of the transformation period Early Mannerist artists reflected this effect to their art. Religion was likewise a direct influence on arts. In the sixteenth century religion was also pregnant to some changes and was criticized. In the beginning of the sixteenth century the masters of High Renaissance were still creating; although they continued on depicting in the same style their art started to show other indications than the stiff canons of the Renaissance due to the historical happenings. What the next generation achieved was to take the indications and construct a new style with the new perception of reality. Each artist of Early Mannerism brought to light his subjective perception therefore displayed a creative character. The most distinguishing feature was their subjectivity instead of the objectivity of the Renaissance. They reflected their interpretation of reality, in itself an epoch-making event. After the dominance of absolute rationality in the Renaissance, intellectuals bewildered to confront with dualities. The artists were overwhelmed with the rational. They started to distort the realities, which took them to excessiveness. VI The stiff perception of the Renaissance reality was being replaced by different realities. The accepted dogmas formerly never been criticized were starting to be shaken. It was a crisis period and artists wanted to find solutions to the crisis of the era, which led them to search for different answers. One-sided view was not satisfying the intellectuals anymore thus they began to possess different angles. The artists were not interested in the ideal beauty as perceived in High Renaissance and found other values to praise. They started to distort and elongate the body, rejected the order, the balance, the perspective rules. They rejected the perspective because it was man's perception. In Renaissance everything was organized according to man but chiefly the scientific innovations proved that the perception which hitherto has been accepted was not right. Man centered world collapsed; the status of man devaluated. This caused insecurity. The intellectuals more aware of the transformation period became neurotic or skeptical. The first signs of capitalist order experienced at the beginning of the sixteenth century brought a positive change in public's becoming more interested in arts. The changing structure of the arts raised the status of the artists and their work became theirs than the demand of their patron. The independent artist was born in mannerist period. The first signs appeared in due course of the personality of the artists of High Renaissance namely with Michelangelo, Leonardo and Raphael. Even though the Early Mannerists inherited a legacy at its peak from the masters of High Renaissance they did not try to imitate the masters but added their characteristics to the innovations. By this way they constructed a new style and even this peculiarity needs to be appreciated. The representatives of the Early Mannerism were Pontormo, Rosso, Beccafumi, Parmigianino and Bronzino. Although Bronzino's works indicate some features of Late Mannerism and Late Mannerists constructed their art on Parmigianino' s they can still be counted as Early Mannerists. Only if their life is observed with a flashback, the change in their style can be revealed. During the second half of the century contrary to the Early Mannerism the arts production was strictly under the control of the court and due to the Counter- Reformation under the control of the church. Unfortunately at this time the arts took an academically character and lost its creativeness. At the beginning of the seventeenth century Mannerism was replaced by Baroque. Although the transformation period was a short lived one it appeared in the crisis periods during the following centuries. All the innovations it sheltered indicate similarities with the twentieth century art, mostly in connection with critical thinking. vn In the movements of the first half of the twentieth century the influences of Mannerism are detected

Manyerizm uluslararası bir hareket olup Floransa'da doğup Roma'ya oradan da diğer Avrupa ülkelerine yayılmıştır. Toskana bölgesi, özellikle Floransa, akımın en temsil edici örneklerini barındırır. Onaltıncı yüzyılın başında öncelikli olarak İtalya'da ve daha sonra diğer Avrupa ülkelerinde sosyal, dini, politik ve kültürel alanlarda bir geçiş dönemi yaşanmaktadır. Bu dönem Rönesans'ın rasyonel, nesnel ve matematiksel gerçeğinin hakimiyetinden hemen sonra yaşanır ve tarihi olayların, coğrafi keşiflerin, teknolojik ve bilimsel buluşların yardımıyla önceki yüzyılın değerleri yenileriyle yer değiştirir. Tarihsel olguların da etkisi ile geçiş dönemi netlikle sanatta gözlemlenir. Geçiş dönemi temsilcileri olan Erken Manyeristler bu etkiyi sanatlarına yansıtırlar. Aynı zamanda dinin de sanat üzerinde yadsınamaz etkisi olmuştur ve onaltıncı yüzyıl başında yeniliklere gebe olup eleştirilmekte idi. Onaltıncı yüzyıl başında Yüksek Rönesans sanatçıları halen üretmekte idiler; her ne kadar stillerini sürdürseler de tarihsel olayların etkisi ile sanatları Rönesans'ın katı kurallarından farklı işaretler göstermeye başladı. Yeni neslin başarısı bu işaretleri alarak yeni bir sanat akımı inşa etmek olmuştur. Her bir Erken Manyerist sanatçı öznel algısını gün ışığına çıkarttı ve böylelikle yaratıcı karakter gösterdi. En ayırd edici özellikleri Rönesans nesnelliğinin yerine öznelliklerini koymalarıdır. Hakikat yorumlan başlı başına dönemsel bir yeniliği ifade etmektedir. Onaltıncı yüzyıl aydınlan Rönesansın mutlak rasyonalliğinden sonra ikilemlerle karşılaşmaktan şaşkındılar. Sanatçılar ise rasyonellikten boğulmuşlardı. Onları aşırılığa götürecek olan gerçekleri çarpıtmayı seçtiler. Katı Rönesans gerçeği başka gerçeklerle yer değiştirmekte idi. Şimdiye kadar hiç eleştirilmemiş ve kabul olagelmiş dogmalar sarsılmaya başlıyordu. Bu bir kriz dönemi idi ve sanatçılar kriz dönemine çözüm bulmak üzere farklı cevaplar aramakta idiler. Artık tek yönlü bakış açısı aydınlan tatmin etmiyordu, böylece farklı açılardan ıx bakmaya başladılar. Onlar Yüksek Rönesans'ın ideal güzelliği ile ilgilenmiyorlardı ve takdir edecek yeni değerler buldular, insan vücudunu uzatıp, çarpıttılar, düzeni ve perspektif kurallarını reddettiler. Perspektifi reddettiler çünkü perspektif insan algılamasının neticesi idi. Rönesans'ta tüm düzen insana göre kurulmuştu fakat özellikle bilimsel yenilikler şimdiye kadar kabul edilmiş olan algılamanın doğru olmadığını kanıtladı. însan merkezli dünya yıkıldı, insana atfedilen değer azaldı. Bu güvensizlik ortamı yarattı. Geçiş döneminin farkında olan aydınlar nörotik ve kuşkucu olmaya başladılar. Onaltıncı yüzyılın başında gözlemlenmekte olan kapitalist dönemin ilk işaretlerinin olumlu yansıması toplumun sanatla daha âzla ilgilenmesi olmuştur. Sanatın değişen yapısı sanatçının değerini arttırmış ve yarattıkları eserler patronun zorlamasındansa kendi yaratılan olmaya başlamıştır. Özgür sanatçı Manyerist dönemde doğar. İlk işaretler Yüksek Rönesans dönemi sanatçılarının, özellikle Michelangelo, Leonardo ve Rapnael'in kişiliklerinde belirir. Erken Manyeristler her ne kadar Yüksek Rönesans ustalarından en yüksek noktasına varmış olan bir miras devralsalar da onları taklit etmeyerek yeniliklere kendi karakterlerini eklemişlerdir. Böylece yeni bir akım oluşturmuşlar ve bu özellikleri bile takdire değerdir. Erken Manyerist temsilciler Pontormo, Rosso, Beccafumi, Parmigianino ve Bronzino'dur. Bronzino'nun bazı eserleri Geç Manyerist özellikler taşısa ve Geç Manyeristler sanatlarını Parmigianino'nun sanatı üzerine kursalar da yinede her iki sanatçı da Erken Manyeristler arasındadırlar. Geçmişleri incelendiğinde stillerindeki değişiklik anlamlandınlabilir. Onaltıncı yüzyılın ikinci yansında sanat üretimi Erken Manyerist döneme karşıt olarak sarayın ve Karşı Reform hareketine bağlı olarak kilisenin otoritesi altına girmiştir. Maalesef sanat bu dönemde akademik bir karakter kazanarak yaratıcılığını yitirmiştir. Onyedinci yüzyıl başında Barok sanat Manyerizmin yerine geçer. Geçiş dönemi kısa sürmüş olsa da takip eden yüzyıllardaki kriz dönemlerinde kendini hissettirir. Barındırdığı tüm yenilikler yirminci yüzyıl sanatı ile eleştirel düşünce bağlamında benzerlik göstermektedir. Yirminci yüzyılbaşı sanat akımlarında Manyerizmin etkileri görülür.
Erken Dönem Manyerist İtalyan Resminde Gerçekliğin Yitirilişi
Thesis (M.A) -- İstanbul Technical University, Institute of Science and Technology, 2001
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2001
Keywords: Fine Arts, Art History,Reality, Manierism, Painting art, Italian painting art; Güzel Sanatlar, Sanat Tarihi, Gerçeklik, Maniyerizm, Resim sanatı, İtalyan resim sanatı